2012
DOI: 10.1002/ibd.21699
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in patients with primary sclerosing cholangitis: Clinical characterization in liver transplanted and nontransplanted patients

Abstract: PSC-IBD may represent a distinct entity of colitis in which low endoscopic activity may mask an active histologic inflammation that possibly contributes to an increased risk of malignancy. Circumstances related to liver transplantation seem to act favorably on colonic inflammation in PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 37 publications
6
80
0
1
Order By: Relevance
“…Interestingly, when a patient undergoes liver transplantation for PSC, their IBD may worsen in severity, raising the issue of whether the presence of PSC has a protective effect on the course of IBD [26,27]. However, a recent study contradicts this, displaying a lower index of clinical activity in those with PSC-IBD who have undergone liver transplantation compared with those who have not [28]. …”
Section: Ibd In Pscmentioning
confidence: 81%
“…Interestingly, when a patient undergoes liver transplantation for PSC, their IBD may worsen in severity, raising the issue of whether the presence of PSC has a protective effect on the course of IBD [26,27]. However, a recent study contradicts this, displaying a lower index of clinical activity in those with PSC-IBD who have undergone liver transplantation compared with those who have not [28]. …”
Section: Ibd In Pscmentioning
confidence: 81%
“…Biopsies should be taken at the index-endoscopy even without macroscopic signs of inflammation (126,131,132).…”
Section: Endoscopic Modalitymentioning
confidence: 99%
“…133,[137][138][139] In the report of Sano et al, 138 11 (55%) of 20 PSC-IBD patients showed right-sided colitis on colonoscopy, and 13 (87%) of 15 showed right-sidepredominant inflammation on histologic examination. On the other hand, some authors reported tendency for pancolitis in PSC-UC, and no statistically significant difference in the frequency of rectal sparing and backwash ileitis, using stricter histologic definitions.…”
Section: Clinicopathologic Characteristicsmentioning
confidence: 96%
“…[140][141][142] Liver transplantation does not appear to reduce either CAC risk or disease activity in this population. 137,143 Therefore, IBD patients with concurrent PSC are subject to immediate annual surveillance colonoscopy and biopsy of the entire colon. 46,142 IBD IN ASIA The incidence and prevalence of IBD in Asia have risen in the last 3 to 4 decades, though they are still lower in Asia than in the West.…”
Section: Cancer Risk and Surveillancementioning
confidence: 99%